Validity and reliability of the WHOQOL-BREF in the measurement of the quality of life of Sickle disease patients in Bahrain - Almarabheh, Amer; Salah, Afif Ben; Alghamdi, Manal; Al Saleh, Aseel; Elbarbary, Abdulla; Al Qashar, Ahmed; Alserdieh, Faisal; Alahmed, Fatema; Alhaddar, Hasan; Alsada, Lulwa; Yosri, Mohamed; Omran, Mahmood; et al. (Frontiers in Psychology, 2023)
Background Limited attention is devoted to the improvement of the quality of life of patients suffering from the negative consequences of Sickle cell disease (SCD). Our study focuses on the evaluation of the performance of the WHOQOL-BREF as a tool to measure the quality of life of SCD Patients in Bahrain. Methods We conducted a cross-sectional study that enrolled 273 SCD patients selected using a simple random sampling technique from primary health-care centers in Bahrain in 2019. A designed questionnaire including the WHOQOL-BREF was filled by the patients in the health centers. The reliability of the WHOQOL-BREF was assessed by standardized Cronbach’s alpha coefficient, and the validity was measured by convergent validity, principal component analysis and confirmatory factor analysis. Results The WHOQOL-BREF had good internal consistency as Cronbach’s alpha coefficient for the overall scale was 0.91. The convergent validity results indicated that the correlation coefficients values for all scale domains are significantly correlated at α < 0.01. Confirmatory factor analysis found that the four-domain structure produced a robust fit to the data. Conclusion The WHOQOL-BREF tool has high internal consistency and validity in assessing the quality of life of Sickle Disease patients in Bahrain.